A model of chemical association in binary mixtures - Castellón Elizondo, Erick (2009)
A general model of chemical association is presented for the correlation of activities of components of a binary mixture A + B with negative deviation from Raoult's law. The model takes into account the coexistence in solution of the species A, B, AB and AB2. The model is applied to the mixture of propanonetrichloromethane, resulting in a satisfactory correlation of the activities. For this system the deviation from ideality can be explained simply by the formation of the AB complex, with H° = (-1.2±0.4) kJ mol-1 and as the standard enthalpy and entropy of association S° = (-34±1) J K-1 mol-1, for the hydrogen bond formation in this system.